Anatomical features, fiber morphological, physical and mechanical properties of three years old new hybrid Paulownia: green Paulownia - H'ng, Paik San; Li, Kun Long; Cheng, Zheng Zhang; Tang, Chao Hui; Wong, Yung Seng; Foo, Shih Lin; Aw, Tong Hun; Wan, Kim Fong (Academic Journals, 2016)
Objective: Green Paulownia (hybridization of Paulownia elongata × Paulownia fotunei and tropical Paulownia spp.) is new hybrid claimed as one of the fast-growing woody plants with the high potential as a fiber material or lignocellulosic material. The material for this study originates from the area of Nanning in China. Methodology: Cell morphology and anatomical appearances were observed and evaluated under the image analysis system (Leica DMLS). Physical and mechanical properties were evaluated based on the American Society for Testing and Materials (ASTM) standards. Results: From the results, average value of the mean fiber length was 0.905 mm, mean fiber length 34.59 μm, lumen thickness 26.80 μm and cell wall thickness 3.89 μm. Fiber dimensions of green Paulownia are in the normal range for hardwoods. The physical and mechanical properties of 3 years old green Paulownia have similar properties than those 7-11 years old Paulownia published in China. Conclusion: The 3 years old green Paulownia timbers can be used as materials for furniture.